Precordial Doppler to assess vascular access in children: A preliminary report. Issue 1 (6th May 2022) - Hirayama, Yuji; Hozumi, Takunori; Aoki, Satoshi; Kojima, Taiki
Abstract: Background: Delayed identification and dysfunction of peripheral intravenous (PIV) infiltration can lead to serious injury in children. This preliminary study aimed to describe the application of precordial Doppler ultrasound to detect and confirm the correct PIV access in children with congenital heart disease (CHD). Methods: This study was conducted on children (<18 years) diagnosed with CHD and admitted to the pediatric intensive care unit (PICU) of a single center after cardiac surgery or cardiac catheterization between February 2020 and May 2021. Three raters judged the precordial Doppler sound change (S test) after injection of 0.5 mL/kg of normal saline (NS) through the PIV access. Blood‐flow velocities before and after the NS injection were recorded and the accuracy of detecting PIV catheter infiltration and dysfunction was analyzed (V test). Results: The overall incidence of PIV infiltration and dysfunction was in 3 out of 103 patients (2.9%). The sensitivity, specificity, positive and negative likelihood ratios, and area under the receiver operating characteristic curve were 3 out of 3 [100%, 95% confidence interval (CI): 29.2–100], 86 out of 100 (86%, 95% CI: 77.6%–92.1), 7.1, 0.0, and 0.93, respectively, in the S test and they were 2 out of 3 (66.7%, 95% CI: 9.4%–99.2), 94 out of 100 (94.0%, 95% CI: 87.4%–7.8%), 11.1, 0.36, and 0.80, respectively in the V test. Conclusions: Precordial Doppler ultrasound was a feasible and accurate technique for confirming correct PIV access in children with CHD; however, a larger, prospective investigation is necessary to examine its diagnostic accuracy.